Male reproductive toxicity of lead in animals and humans. ASCLEPIOS Study Group. Issue 6 (June 1998) - Apostoli, P; Kiss, P; Porru, S; Bonde, J P; Vanhoorne, M
Abstract : OBJECTIVE: To critically review the literature on male reproductive toxicity of lead in animals and humans. METHODS: A systematic literature search identified a total of 32 experimental studies in animals and 22 epidemiological studies, one case report on humans and five review articles or documents. The studies were evaluated by paying attention mainly to sample size, study design, exposure, and dose characterisation, analytical method standardisation, and quality assurance. RESULTS: Several studies on rats and other rodents indicated that blood lead concentrations > 30-40 micrograms/dl were associated with impairment of spermatogenesis and reduced concentrations of androgens. However, other animal studies, mainly about histopathological, spermatozoal, and hormonal end points, indicated that certain species and strains were quite resistant to the reproductive toxicity of lead and that different testicular lead concentrations could account for these differences. The human studies focused mainly on semen quality, endocrine function, and birth rates in occupationally exposed subjects, and showed that exposure to concentrations of inorganic lead > 40 micrograms/dl in blood impaired male reproductive function by reducing sperm count, volume, and density, or changing sperm motility and morphology. No relevant effects were detected on endocrine profile. CONCLUSION: Several factors make it difficult to extrapolate the animal data to the human situation. The difficulties are mainly due to differences between species in reproductive end points and to the level of exposure. Concentrations of blood lead > 40 micrograms/dl seemed to be associated with a decrease in sperm count, volume, motility, and morphological alterations and a possible modest effect on endocrine profile. Dose-response relation, in particular at a threshold level, is poorly understood, and site, mode, or mechanism of action are unknown. Also, the effects were not always the same or associated in the same on sperm count and concentration. Some methodological issues and indications for future studies are discussed.